Analisis Strategi Pemasaran Dalam Meningkatkan Penjualan Pasca Covid-19 Studi Kasus Pada Dealer Mobil Honda Arista Thamrin Medan) - Lubis, Listiya Andana; Ramadhani, Sri; Syarvina, Wahyu (Universitas Labuhanbatu, 2023)
This research was conducted with the aim of finding out how the car marketing strategy at the Honda Arista Thamrin Medan car dealer increases sales and to find out the obstacles in implementing marketing strategies at the Honda Arista Thamrin Medan car dealer in increasing sales. The results of the research show that the marketing strategy (Marketing Mix) in increasing the number of post-Covid-19 car sales at the Honda Arista Thamrin Car Dealer has experienced an increase and decrease in sales for 5 years, namely in 2018 the number of products sold was 338 units, in 2019 there was a decrease in sales products sold were 184 units, in 2020 there was a decrease in sales of products sold by 150 units, in 2021 there was an increase in product sales of 177 units, in 2022 there was also an increase in sales of products sold by 266 units. Obstacles in implementing marketing strategies (Marketing Mix) The impact of post-covid-19 is one of the impacts that is very influential in increasing product sales where after post-covid-19 sales experience ups and downs in product sales and where competition with other automotive brands is also an obstacle in implementing strategies marketing.